1996
DOI: 10.1080/095530096145283
|View full text |Cite
|
Sign up to set email alerts
|

HPRT mutations in V79 Chinese hamster cells induced by accelerated Ni, Au and Pb ions

Abstract: Mutation induction by accelerated heavy ions to 6-TG resistance (HPRT system) in V79 Chinese hamster cells was investigated with Ni (6-630 Me V/u), Au (2.2, 8.7 Me V/u) and Pb ions (11.6-980 Me V/u) corresponding to a LET range between 180 and 12895 ke V/microns. Most experiments could only be performed once due to technical limitations using accelerator beam times. Survival curves were exponential, mutation induction curves linear with fluence. From their slopes inactivation- and mutation-induction cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…At 100 keV/μm, average separation density between ionizing events from single hits roughly coincides with the DNA double helix diameter, i.e., 2 nm (20 Å) and has the greatest probability of causing a double-strand break which is the basis for most biologic effects (Hall and Hei, 2003). This study also confirms the findings of Stoll et al (1995Stoll et al ( , 1996 who found an RBE for cell survival by high LET nickel ions (>1000 keV/μm) around 1.…”
Section: Cellular Survival After Heavy Ions Exposuresupporting
confidence: 89%
“…At 100 keV/μm, average separation density between ionizing events from single hits roughly coincides with the DNA double helix diameter, i.e., 2 nm (20 Å) and has the greatest probability of causing a double-strand break which is the basis for most biologic effects (Hall and Hei, 2003). This study also confirms the findings of Stoll et al (1995Stoll et al ( , 1996 who found an RBE for cell survival by high LET nickel ions (>1000 keV/μm) around 1.…”
Section: Cellular Survival After Heavy Ions Exposuresupporting
confidence: 89%
“…For LETs above 900 keV/μm, RBE values for reproductive cell death dropped to 1 or below 1. Stoll et al ( 159 ) also found an RBE for inactivation by high LET lead ions (>10,000 keV/μm) far below 1 and for nickel ions (>1000 keV/μm) around 1. In a human neuronal progenitor cell line (Ntera2), the RBE max for apoptosis 48 h after iron ion exposure (1 GeV/n) was at least 3.4 ( 160 ).…”
Section: Influence Of Linear Energy Transfer On Transcription Factor mentioning
confidence: 92%
“…The DNA solutions were desicated at room temperature. With a molecular mass of 667 g/mol per nucleotide pair and a plasmid size of 3199 base pairs, one can calculate the volume of a plasmid to be about 1.5×10 -5 µm 3 [5]. The sample contained 2.9×10 11 plasmid molecules.…”
Section: Ion Beam Irradiationmentioning
confidence: 99%